The morphology, size and density of the touch dome in human hairy skin by scanning electron microscopy. (12th March 2019) - Kabata, Yudai; Orime, Mari; Abe, Riichiro; Ushiki, Tatsuo
Abstract : We examined the shape, size, and density of the touch dome of human skin of the forearm and the abdomen through scanning electron microscopy. Our results suggested that the regional difference in size and density of the touch dome might be related to the sensation's sensitivity as touch spots. Abstract: The touch domes of mammalian hairy skin are mechanoreceptors characterized by the accumulation of Merkel cell-neurite complexes at the epidermal base. In this study, we examined the shape, size, and density of the touch dome of human skin of the forearm and the abdomen through scanning electron microscopy (SEM). Human skin samples were obtained from donated bodies, as well as a patient who underwent biopsy. Skin pieces were treated with a KOH-collagenase method for the separation of the epidermis from the dermis. The basal surface of the separated epidermis was then observed using SEM. The touch dome was clearly determined as a concave area bordered by a thick epidermal ridge, where neural components accumulated. The touch dome was rather independent from hair follicles, although they were sometimes located beside the touch dome. The average size and density of the touch dome were 0.06 mm 2 and 3.82 cm 2 in the forearm, and 0.10 mm 2 and 1.30 cm 2 in the abdomen, respectively. Our results suggested that the regional difference in size and density of the touch dome might be related to the sensation's sensitivity as touch spots in human hairy skin.